The Two Sides of Transfer in the Light of Psychotypology - Ölbei, Claudia (SlavVaria, 2026)
The Two Sides of Transfer in the Light of Psychotypology. The acquisition of foreign languages poses a considerable challenge for native speakers of non-Indo-European languages; consequently, the employment of multilingual learning strategies is imperative. The prerequisites for the utilisation of these strategies are language awareness, crosslinguistic influence (CLI) and psychotypology. The results of a questionnaire administered to students at the University of Pécs, in the context of a broader scale survey involving 300 respondents, provide evidence that the majority of respondents perceive similarities between their foreign languages and almost two-thirds of them answered positively to the question whether these similarities helped them in learning new languages. However, it is crucial to recognise the so-called similarity paradox, which can result in negative transfer (interference). The present article will concentrate on responses, with the purpose of illustrating typical mistakes attributed to the influence of previously acquired languages.